Effect of post-slaughter time and storage conditions on chemical and microbial changes in locally marketed beef - Jahan, R; Hossain, MM; Rashid, MH; Akhter, S; Khan, MSI (Bangladesh Journal of Animal Science, 2015)
Fresh meat is commonly marketing at environmental temperature for long time in many developing countries including Bangladesh. The present study was conducted to assess whether elapsed time between slaughter and preservation and storage conditions influence the chemical and microbial changes of locally marketed beef. Meat samples were collected from local markets and divided into two groups, morning and evening beef. Morning beef was collected immediately after slaughtering from healthy cattle while evening one was collected 8 h after slaughtering. The samples were kept either in refrigerator (4oC) or freezer (-20oC). Refrigerated samples were stored for 7 days and analyzed on day1st, 3rd and 7th while frozen samples were stored for 90 days and analyzed on day 3rd, 45th and 90th. Results showed that there was a significant difference in chemical and microbial parameters between morning and evening beef (p<0.01 to 0.05). With respect to the advances of storage time, the dry matter, crude protein, ether extract and ash contents were increased in beef sample (p<0.01), indicating the moisture loss from meat time elapsed after slaughtering. Moreover, the coliform, yeast and mold counts were also increased with advance of storage time (p<0.01 to0.05),indicating the unhygienic conditions of slaughter house, equipment and water which is giving signal for the possible occurrence of food borne intoxication. In conclusion, we found that the quality of marketed beef degraded with the time elapsed before storage and storage temperature suggesting the importance of early preservation of meat at lower temperature. Our findings of increased number of microbial counts were also suggested the necessity to improve the hygienic conditions of slaughterhouse and equipment in developing countries like Bangladesh. DOI: http://dx.doi.org/10.3329/bjas.v44i1.23143 Bang. J. Anim. Sci. 2014. 44 (1): 52-58